1994
DOI: 10.1039/p19940000083
|View full text |Cite
|
Sign up to set email alerts
|

An efficient and selective palladium-catalysed oxidative dicarbonylation of alkynes to alkyl- or aryl-maleic esters

Abstract: Terminal alkyne dicarbonylation can be readily effected under mild conditions b y treating alkynes with carbon monoxide and alcohols or water at 25-80°C in the presence of Pdlp, KI and air, with unprecedented catalytic efficiency. Dicarbonylated products are mainly maleic esters or acids and their ring-chain tautomers. The latter are formed to a large extent at room temperature. Reaction pathways are discussed.Dicarbonylation of alkynes with carbon monoxide has been known for several years,' but even the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
96
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(103 citation statements)
references
References 17 publications
(2 reference statements)
5
96
0
2
Order By: Relevance
“…Gabriele et al [19] have previously reported the oxidative carbonylation of a variety of alkynes using PdI 2 /KI and palladium iodidethiourea (tu) catalysts with a thiourea/palladium ratio of 3 or 3. 2-is likely to be at least partially dissociated in methanol solution [18,19]. The mechanism of phenylacetylene carbonylation, as reported by Gabriele [18], is given in Eqs.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Gabriele et al [19] have previously reported the oxidative carbonylation of a variety of alkynes using PdI 2 /KI and palladium iodidethiourea (tu) catalysts with a thiourea/palladium ratio of 3 or 3. 2-is likely to be at least partially dissociated in methanol solution [18,19]. The mechanism of phenylacetylene carbonylation, as reported by Gabriele [18], is given in Eqs.…”
Section: Resultsmentioning
confidence: 88%
“…2-is likely to be at least partially dissociated in methanol solution [18,19]. The mechanism of phenylacetylene carbonylation, as reported by Gabriele [18], is given in Eqs. 1-4 (Scheme 1).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Water has been shown to affect the behavior of the catalytic system used in the PCPOC reaction and is therefore proposed to be involved in the processes in the reaction mechanism that produce the pH oscillations [9,10]. Water also reacts in a similar manner to methanol (Scheme 1) leading to the isomeric diacids [(2Z)-2-phenyl-2-butenedioic acid and (2E)-2-phenyl-2-butenedioic acid] and phenylmaleic anhydride [11].…”
Section: Introductionmentioning
confidence: 99%
“…Using a PdI 2 -KI catalyst with alkynes under mild conditions, high catalytic efficiencies have been achieved leading to a mixture of dicarbonylation products [2]. When phenylacetylene (PhAc) was used as the substrate in methanol (palladium-catalyzed phenylacetylene oxidative carbonylation, PCPOC), oscillations in pH, redox potential and gas uptake (CO and O 2 ) were discovered [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%